Attention deficit hyperactivity disorder in adults and the role of the mental health nurse. (2nd February 2019) - Adams, Danielle; Padmore, Jane; Singh, Promilla
Abstract : The prevalence of attention deficit and hyperactivity disorder diagnosis appears to have increased in recent years, with much discussion on the subject in the popular press. This article discusses the role of mental health nurses in the management of this often underdiagnosed and undertreated condition in adults, taking account of extended roles such as non-medical prescribers and the recently published clinical guideline by the National Institute for Health and Care Excellence. There is a continued need to support shared decision making, encourage adherence to treatment and reduce the negativity surrounding the use of controlled drugs to manage this condition. Children who have a diagnosis of attention deficit and hyperactivity disorder will generally have had comorbid difficulties considered as part of the diagnosis and treatment plans, with input from education in addition to health and social care. In adulthood, it could be argued that the focus is on managing substance abuse, mood and anxiety disorders, resulting in the diagnosis of attention deficit and hyperactivity disorder being overlooked.